2012
DOI: 10.1016/j.atherosclerosis.2012.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Apo E4 and lipoprotein-associated phospholipase A2 synergistically increase cardiovascular risk

Abstract: Objective Apolipoprotein E (apoE) has been implicated as conveying increased risk for coronary artery disease (CAD). Previous studies suggest a role of apoE as a modulator of immune response and inflammatory properties. We hypothesized that the presence of apo E4 is associated with an increased inflammatory burden in subjects with CAD as compared to subjects without CAD. Methods ApoE genotypes, systemic (C-reactive protein [CRP], fibrinogen, serum amyloid-A [SAA]) and vascular inflammatory markers (Lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The gene locus for the three major ApoE alleles (E2,E3,E4) is located on chromosome 19q13.2 and the E4 allele has been validated as a strong predictor for Alzheimer's disease. 15 Furthermore, ApoE variants increase cardiovascular disease risks by altering vascular inflammation, 16 and patients carrying the E4 allele are more likely to require CABG at a younger age. 17 In chronic renal failure, Arikan et al showed an association between ApoE genotypes an atherogenic lipid levels in dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…The gene locus for the three major ApoE alleles (E2,E3,E4) is located on chromosome 19q13.2 and the E4 allele has been validated as a strong predictor for Alzheimer's disease. 15 Furthermore, ApoE variants increase cardiovascular disease risks by altering vascular inflammation, 16 and patients carrying the E4 allele are more likely to require CABG at a younger age. 17 In chronic renal failure, Arikan et al showed an association between ApoE genotypes an atherogenic lipid levels in dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although traditionally considered clinically distinct from each other with mutually exclusive mechanisms [3] , late-onset AD is increasingly regarded as a pathological process that is strongly influenced by cerebrovascular dysfunction. Even the major single gene associated with increased late-onset AD risk, APOE , was earlier identified as a risk gene for cardiovascular diseases [4] . The pathogenic mechanisms underlying these two conditions appear to be connected through cerebral hypoperfusion, blood–brain barrier compromise, inflammatory cell infiltration and hemorrhagic susceptibility [59] .…”
mentioning
confidence: 99%
“…In this case, the biggest fraction was also albumins (65−70 kDa) (He et al, 1992), but we can observe differences between sample 2 and sample 3: in both of them, protein of 25−30 kDa is presented. According to Gungor et al (2012), apolipoprotein E (APOE) can play an important role in increasing the risk of coronary heart disease; APOE is a 299 amino acids long, arginine-rich protein at 34.2 kDa weight (Ćwiklińska et al, 2015). Previous studies were related only to the study of the concentration of apoE and Lp-PLA 2 in blood plasma of patients using standard clinical procedures.…”
Section: Resultsmentioning
confidence: 99%